When and how to use confirmatory composite analysis (CCA) in second language research - Alamer, Abdullah (2024)
Alamer, A., Schuberth, F., & Henseler, J. (2024). When and how to use confirmatory composite analysis (CCA) in second language research. Studies in Second Language Acquisition, 46(2), 597–616. Advance online publication. https://doi.org/10.1017/S0272263124000020 --- This work was supported by the Deanship of Scientific Research, Vice Presidency for Graduate Studies and Scientific Research, King Faisal University, Saudi Arabia [Grant No. 5589]. Jörg Henseler acknowledges a financial interest in the composite-based SEM software ADANCO and its distributor, Composite Modeling. Moreover, he gratefully acknowledges financial support from FCT Fundação para a Ciência e a Tecnologia (Portugal), national funding through a research grant from the Information Management Research Center– MagIC/NOVA IMS (UIDB/04152/2020). Moreover, we thank Daniel Ondé and colleagues for giving us permission to use their dataset in our illustrative example. We also thank Alexandra Elbakyan for her efforts in making science accessible.